The Efficacy of (810 Nm) Diode Laser in Treatment of Idiopathic Epistaxis - Khammas, Ammar H. (Iraqi Journal of Laser, 2019)
There are many causes for epistaxis but it is mainly idiopathic in type. In Management of epistaxis there are different modality either medical or cautery(chemical or galvanic) recently laser is used in management of epistaxis. The type of laser used in current study was 810 nm diode laser. The aim of the study is to evaluate its efficiency in control of active and non active idiopathic epistaxis; The design of the study is interventional therapeutic trial. The study was performed from December 2011 to December 2012 in Al Yarmouk teaching hospital at otorhinolaryngology department. In current study the diode laser is used in different power with same exposure time in all application; The power density is measured and choose the best one to stop both active and non active bleeding. The modality is compared with galvanic electrical cautery used in treatment of epistaxis. the comparison depends on the side effect and the complication of each modality.